1995
DOI: 10.1164/ajrccm.152.6.8520733
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune phenomena in bronchial asthma with special reference to aspirin intolerance.

Abstract: We assessed the autoimmune status of 185 adult patients with bronchial asthma and 46 healthy subjects of similar sex and age. The patients were divided into groups with: (1) aspirin-induced asthma (AIA) (n = 80); (2) intrinsic asthma with good aspirin tolerance (n = 46); and (3) atopic asthma (n = 59). Antinuclear antibodies (ANA) at a titer of > or = 1:40 were present in the serum of 55% of the patients with AIA, 41% of those with intrinsic asthma, 39% of those with atopic asthma, and 11% of the healthy subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 11 publications
1
51
0
1
Order By: Relevance
“…Cross-linking of the IgE-loaded high-affinity IgE receptor by multivalent antigens results in mast cell activation and subsequent release of multiple proinflammatory mediators [20]. The autoantibodies against FcεRI or IgE may be involved in the pathogenesis of asthma [17,18,19]. We found that 28.6% of asthma patients revealed positive autoantibodies against FcεRI or IgE, suggesting that autoimmunity may be involved in the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-linking of the IgE-loaded high-affinity IgE receptor by multivalent antigens results in mast cell activation and subsequent release of multiple proinflammatory mediators [20]. The autoantibodies against FcεRI or IgE may be involved in the pathogenesis of asthma [17,18,19]. We found that 28.6% of asthma patients revealed positive autoantibodies against FcεRI or IgE, suggesting that autoimmunity may be involved in the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The possible involvement of autoimmunity in the pathogenesis of asthma has been proposed by few studies [15,16,17,18,19]. FcεRI is a multimeric surface receptor that is expressed exclusively as a tetramer on rodent cells, but exists as a tetramer or trimer on human cells.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of a possible involvement of autoimmunity in the pathogenesis of asthma has been proposed by earlier studies that demonstrated higher incidences of various autoantibodies against antigens in bronchial mucosa, paranasal sinus, lung, endothelial cells, and nuclei in patients with asthma, compared with healthy control subjects (7)(8)(9)(17)(18)(19). However, these observations could not establish a causal relationship between autoimmunity and asthma, partly due to lack of an identified autoantigen or lack of a logical association between these autoantibodies and airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, asthma developed into the Churg-Strauss syndrome, a distinct form of systemic vasculitis characterized by eosinophilia, lung infiltration, paranasal sinus abnormality, and neuropathy (27). Rheumatic symptoms were reported to be more common among the patients with asthma with antinuclear antibodies (19). These observations suggest that asthma might be a systemic inflammatory disease in a subgroup of patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of a possible involvement of autoimmunity in the pathogenesis of asthma has been proposed by few studies as already reviewed above. Szczeklik et al [19]assessed the autoimmune status of 185 adult patients with bronchial asthma and 46 healthy subjects of similar sex and age. The patients were divided into groups with aspirin-induced asthma, intrinsic asthma with good aspirin tolerance, and atopic asthma.…”
Section: Common Pathogenic Mechanismsmentioning
confidence: 99%